Relationship some Alantherpoumitrih variables and Elkinmetekih handball players in the javelin throw the ball and spear - mataib , saher (Journal of Physical Education, 2012)
The research aims to research aims to find out the relationship between some variables Anthropometric players handball in throwing the ball and spear and also research aims to find out the relationship between some variables Elkinmetekih players handball in throwing the ball and spear, using radar device type (Sport Radarhta) (SR 3600), The sample consisted of (5) players from the squad University, was selected way intentional, was carried out one test, and after receiving the results of the analysis, the researcher extracted statistical means to them, and concluded as follows: there is a direct correlation between the weight of the player with a spear, and also there is a direct correlation between the length of the arm with the speed of the ball, and also there is a direct correlation between the total length with the speed of the ball. The researcher recommended the following: give educational exercises for handball player on how to throw a spear, and also conduct similar studies on some Elkinmetekih variables and Alantrbumitrih not addressed by the researcher in the researched this as well as other events.